2013
DOI: 10.1124/dmd.113.051482
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variability of Carboxymethylenebutenolidase Homolog, a Novel Olmesartan Medoxomil Hydrolase, in the Human Liver and Intestine

Abstract: Olmesartan medoxomil (OM) is a prodrug-type angiotensin II type 1 receptor antagonist. OM is rapidly converted into its active metabolite olmesartan by multiple hydrolases in humans, and we recently identified carboxymethylenebutenolidase homolog (CMBL) as one of the OM bioactivating hydrolases. In the present study, we further investigated the interindividual variability of mRNA and protein expression of CMBL and OM-hydrolase activity using 40 individual human liver and 30 intestinal specimens. In the intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(29 reference statements)
1
4
0
1
Order By: Relevance
“…The next predicted gene is CMBL , which encodes a specific cysteine hydrolase of the dienelactone hydrolase family and normally has high expression in liver cytosol but not in breast tissues [43,44]. In 2014, an early study on proteasome function in breast cancer confirmed that cysteine hydrolase has an abnormal expression level in certain breast cancer subtypes, and this finding corresponds with our prediction [45].…”
Section: Discussionsupporting
confidence: 79%
“…The next predicted gene is CMBL , which encodes a specific cysteine hydrolase of the dienelactone hydrolase family and normally has high expression in liver cytosol but not in breast tissues [43,44]. In 2014, an early study on proteasome function in breast cancer confirmed that cysteine hydrolase has an abnormal expression level in certain breast cancer subtypes, and this finding corresponds with our prediction [45].…”
Section: Discussionsupporting
confidence: 79%
“…In general, other poorly studied metabolic enzymes stand to benefit similarly from PAE identification via cABPP as most well-characterized metabolic enzymes are amenable to the standard suite of mechanism-based inhibitors used in reaction phenotyping studies. The recent discovery of the sparsely studied hydrolase CMBL as a PAE for the antihypertensive prodrug olmesartan medoxomil , illustrates that numerous enzymes with unique and exploitable specificities remain unidentified. We hope that the experiments herein represent the first study of many in which researchers use cABPP for PAE identification.…”
Section: Discussionmentioning
confidence: 99%
“…For olmesartan measurement, the Captiva filtrate was mixed with 200 ml of 50% methanol containing 1% formic acid, and was analyzed by liquid chromatography-tandem mass spectrometry consisting of a Prominence LC-20A system (Shimadzu, Kyoto, Japan) and an API3200 (Applied Biosystems/ MDS SCIEX, Foster City, CA) as previously reported (Ishizuka et al, 2013). For candesartan and azilsartan measurements, the filtrate was directly analyzed by liquid chromatography-tandem mass spectrometry consisting of a Prominence CBM-20A system (Shimadzu) and an API4000 (Applied Biosystems/ MDS SCIEX).…”
Section: Bioactivation Of Arb Prodrugs By Cmbl and Ces1mentioning
confidence: 99%